Potential of renewable energy biogas from plant (Hyacinth) - Riswanto Riswanto; Sodikin Sodikin (Journal of Physics: Theories and Applications, 2018)
Energy is one of the basic human needs, both in the form of electricity and energy in the form of heat / gas. The increase in Indonesia's population has increased by 1.3% every year, this is comparable to the increase in energy needs. Current conditions illustrate that the fulfillment of energy needs is sourced more from fossil materials that cannot be renewed, therefore a solution is needed to overcome these problems by finding and finding potential alternative energy sources that can meet human needs. One of the energy that can be utilized is biogas. Biogas is a process of fermentation of organic matter that produces methane gas. Organic materials available in nature are abundant, one of which is organic matter derived from water hyacinth. For this reason, a research study is needed by identifying the potential of biogas energy from water hyacinth. This research is an experimental research, the data collection technique is done by quantitative methods. The tools needed are a manometer, thermometer and biogas reactor. This research was conducted by measuring the temperature and pressure produced by biogas made from organic water hyacinth. The results obtained showed that the biogas produced from water hyacinth produced a gas odor that was relatively not too stinging and the gas formation process was faster. Gas pressure measurements are carried out using a monometer by calculating the difference in the height of water pressure in the U pipe. Measurements of pressure changes are carried out for 20 days by conditioning external factors such as temperature and humidity. The study was conducted to examine the effect of adding water hyacinth to biogas organic matter. The results obtained that t count> t table is the value of t arithmetic (8.183)> t table (2.093) and the significance level of 0.000 <0.05. This means that there are differences in biogas production between before adding water hyacinth and after adding water hyacinth.